Dermatomyositis following COVID‐19 vaccination: Temporal or causal association?. Issue 1 (2nd January 2023) - Ouni, Nour E. I.; Lahouel, Maha; Ben Salah, Nesrine; Mokni, Sana; Sriha, Badreddine; Belajouza, Colandane; Denguesli, Mohamed
Abstract: Several cutaneous complications have been reported with COVID‐19 vaccines. Most of them are benign and consist mainly of delayed local reactions, urticaria, and morbilliform eruptions. Dermatomyositis (DM) is a multi‐system autoimmune disorder primarily affecting the skin, skeletal muscle and blood vessels. We describe a rare case of DM after administering the first dose of the Pfizer‐BioNTech COVID‐19 vaccine. The causal relation was suggested based on the timing of the onset and the absence of other triggering factors.